Civic Engagement and Politics 2019
DOI: 10.4018/978-1-5225-7669-3.ch047
|View full text |Cite
|
Sign up to set email alerts
|

Children and Youth Making Digital Media for the Social Good

Abstract: This chapter describes how children and youth are using digital media to address inequity in their schools, communities, and in society. The chapter begins with a review of the historical and cultural roots of children making digital media for the social good, and situates the approach in the context of other civic and community-based movements. The next section focuses on the range of ways that children and youth are making digital media, including who is participating, and the social and institutional factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The power of images highlights the dynamics of youths' relationship to physical places and the spaces that they create through forging relationships with one another. Researchers have consistently observed that the images that young adults capture not only serve as a means for increasing youth participation in civic life but also influencing change in a community (e.g., Denner & Martinez, 2015).…”
Section: Digital Storytelling Identity Formation and Voicementioning
confidence: 99%
See 1 more Smart Citation
“…The power of images highlights the dynamics of youths' relationship to physical places and the spaces that they create through forging relationships with one another. Researchers have consistently observed that the images that young adults capture not only serve as a means for increasing youth participation in civic life but also influencing change in a community (e.g., Denner & Martinez, 2015).…”
Section: Digital Storytelling Identity Formation and Voicementioning
confidence: 99%
“…That is, it is one thing to encourage youth to reflect on their own sense of agency and voice and to promote discussions of responsible citizenship and engagement using the tools of digital storytelling and photovoice. It is quite another to focus on the structural problems that affect the unequal power dynamics that have erased certain histories, culture, and traditions (Tuck, 2013); to examine the unequal distribution of resources in schools and neighborhoods (Denner & Martinez, 2015); to analyze the ways in which a lack of environmental justice has affected the health and well-being of children and families (Hackett et al, 2015); or to address the ways that research itself can reproduce the very conditions of injustice that it seeks to disrupt (Tuck & Yang, 2014). In cases such as the above, the gaze, as Tuck (2013) explains, is not on young people but on the institutions, structures, and ideologies that would otherwise silence, marginalize, and erase histories of laws and policies that oppress youth and their families.…”
Section: Help Youth Understand the Sociopolitical Contexts Of Communimentioning
confidence: 99%